Analysis of The Maturity Level of Cyber Security in The Context of Personal Data Protection for MSMEs in Depok City - Catur Agus Sulistyo; Gerry Firmansyah; Budi Tjahjono; Agung Mulyo Widodo (Green Publisher Indonesia, 2025)
This research explores the cybersecurity maturity level in the context of personal data protection for Micro, Small, and Medium Enterprises (MSMEs) in Depok City, Indonesia. The increased use of digital technology by MSMEs has raised concerns about personal data security and the vulnerability to cyberattacks. This study aims to develop an assessment tool that MSMEs can use to evaluate their compliance with the Personal Data Protection (PDP) Law and measure their readiness to face cybersecurity challenges. Through a combination of qualitative and quantitative methods, the study analyzes MSMEs' preparedness for cybersecurity and compliance with the PDP Law. The results reveal that while 60.2% of MSMEs manage personal data, a significant 93.5% have not complied with the PDP Law, exposing them to potential financial losses and cyber risks. The research emphasizes the need for MSMEs to adopt a simple yet effective cybersecurity framework to ensure data protection and compliance.